Prediksi Jumlah Persediaan Telur Ayam Menggunakan Metode K-Neares Neighbor: - - baguna, filda; Husdi, Husdi; Taliki, Sunarto; Kamaruddin, Andi (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Abstract - UD. Unggas Karya Mandiri is one of the production areas producing chicken eggs in Banggai Laut Regency, with the existence of UD Unggas Karya Mandiri Banggai Laut which has the aim of increasing the number and types of employment opportunities for Banggai Laut Regency in particular. Based on the results of research at UD Unggaas Karya Mandiri Banggai Laut, this is the result of fluctuating chicken egg production or unstable production which is caused by several things, namely lack of availability of feed ingredients, anti-biotic drugs, vaccinations and so on. The aim of this research is to obtain better accuracy in predicting the number of chicken egg supplies at UD Unggas Karya Mandiri Banggai Laut by applying the K-Nearest Neighbor method. Based on the prediction results with existing data, it was obtained using the K-Nearest Neighbor method. This application was able to predict the number of chicken egg supplies at UD Unggas Karya Mandiri. It can be seen that the prediction application for the number of chicken egg supplies at UD Unggas Karya Mandiri Banggai Laut can be applied with an accuracy of 96.98% of the prediction results obtained.. Keywords: Prediction, Eggs, Accuracy, Inventory, K-Nearest Neighbor